2013
DOI: 10.1016/j.foodchem.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of highly enriched 13C-lycopene for human metabolic studies using repeated batch tomato cell culturing with 13C-glucose

Abstract: While putative disease-preventing lycopene metabolites are found in both tomato (Solanum lycopersicum) products and in their consumers, mammalian lycopene metabolism is poorly understood. Advances in tomato cell culturing techniques offer an economical tool for generation of highly-enriched 13C-lycopene for human bioavailability and metabolism studies. To enhance the 13C-enrichment and yields of labeled lycopene from the hp-1 tomato cell line, cultures were first grown in 13C-glucose media for three serial bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Thus, we are limited to small but strategic studies of limited statistical power to test bioavailability and tissue distribution. Methodological improvements to improve yield and the use of stable isotopes are already being made and will enhance the ability of investigators to elucidate the metabolism of bioactive carotenoids and their biological importance (25,31,51). Stable isotope carotenoids are better suited for future metabolite identification based on signal strength, potential for analysis in shared MS facilities, and safety in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we are limited to small but strategic studies of limited statistical power to test bioavailability and tissue distribution. Methodological improvements to improve yield and the use of stable isotopes are already being made and will enhance the ability of investigators to elucidate the metabolism of bioactive carotenoids and their biological importance (25,31,51). Stable isotope carotenoids are better suited for future metabolite identification based on signal strength, potential for analysis in shared MS facilities, and safety in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Extinction coefficients and characteristic absorption spectra of carotenoids and respective geometrical isomers were previously published (26)(27)(28)(29)(30)(31).…”
Section: Carotenoid Analysis Of Dietmentioning
confidence: 99%
“…It has been shown that extrinsic labeling can be used for nonheme iron (as in plant foods) and zinc absorption studies in humans . Numerous studies have also investigated carotenoid metabolism using 14 C‐ and 13 C‐labeled compounds . Unfortunately, the high cost of these compounds and the labor‐intense procedures required have limited their use.…”
Section: In Vivo Bioavailability and Bioconversion Methodsmentioning
confidence: 99%
“…[37][38][39][40][41] Numerous studies have also investigated carotenoid metabolism using 14 C-and 13 C-labeled compounds. [42][43][44][45][46][47][48][49][50][51] Unfortunately, the high cost of these compounds and the labor-intense procedures required have limited their use.…”
Section: Human Studiesmentioning
confidence: 99%
“…The context of the meal where cruciferous vegetables are consumed may also impact host exposure to bioactives . In recent years, many studies are showing exceptionally diverse pharmacokinetics of phytochemicals in humans as host genetics impact the metabolism and degradation of phytochemicals . Furthermore, epidemiologic studies must consider the exposures to known bladder carcinogens as critical variables and examine key interactions with diet and host genetic polymorphisms associated with carcinogen metabolism.…”
Section: Epidemiology Of Cruciferous Vegetables Isothiocyanates Andmentioning
confidence: 99%